DIGITAL MARKETING AND PERFORMANCE OF SMALL AND MEDIUM ENTERPRISES IN NIGERIA - Iherobiem, Augustine Chibueze; Kalejaiye, Oluwadamilare Oladipupo (Jurnal Ekonomi dan Bisnis Airlangga, 2025)
Introduction: The study examined the effect of digital marketing on the performance of SMEs in Nigeria. The digital marketing techniques examined in the study include social media marketing, email marketing, and content marketing, and were anchored on the resource-based view theory. Methods: The study's methodology was guided by the positivist research philosophy, and a descriptive survey research design was also employed. The study's population consists of managers and owners of small businesses in Ogun State's Ijebu Ode area. A purposive sampling technique was used, and a sample size of 200 was adopted. The study's response rate is 87.5%, and both descriptive and inferential statistics were used to evaluate the data. Results: According to the results of the regression analysis, there is a significant and positive relationship between digital marketing and the performance of SMEs, with digital marketing improving SMEs' performance by 45.6%. Conclusion and suggestion: Based on the results, it was recommended that SMEs' management use content marketing to effectively attract customers to their products, integrate social media into their business plan, and design their emails in a way that makes them highly appealing to readers.